Global analysis of in situ cosmogenic 26Al and 10Be and inferred erosion rate ratios in modern fluvial sediments indicates widespread sediment storage and burial during transport - C. T. Halsted; P. R. Bierman; A. T. Codilean; L. B. Corbett; M. W. Caffee (Geochronology)
Since the 1990s, analysis of cosmogenic nuclides, primarily 10Be, in quartz-bearing river sand has allowed the quantitative determination of landscape mass loss rates (hereafter, erosion rates) at a basin scale. Paired measurements of in situ cosmogenic 26Al and 10Be in sediment are less common but offer insight into the integrated exposure and burial history of sediment moving down slopes and through drainage basins. Prolonged burial (>105 years), a violation of assumptions underlying erosion rate calculations, is indicated by higher 26Al-based than 10Be-based erosion rates due to preferential loss of shorter-lived 26Al by decay when quartz is at least in part shielded from cosmic rays.